(untitled) (Sains Humanika, 2022)
This study aimed to find out the teacher’s perceptions about the suitability and strengths and weaknesses of the CEFR aligned textbook, Get Smart Plus 3 textbook used for Year 3 students in Malaysian schools. A mixed-method approach was employed in this research in which an eclectic checklist was used for the quantitative part while semi-structured interview was conducted for the qualitative part. 36 respondents were involved in the quantitative part, while two Year 3 teachers were interviewed. The findings showed that the Get Smart Plus 3 textbook is highly useful for the learners in terms of general attributes, vocabulary, grammar, language skills, activities, and supplementary materials. However, foreign culture and contexts used in the textbook need to be reviewed as the teachers found these elements to be of concern for the students. The findings can help materials writers and the curriculum development unit to reevaluate and improve on the textbooks to suit the Malaysian context.